Characterization and enhanced antibiofilm activity of Annona muricata extract in combination with fluconazole against Candida albicans - Abhay Mishra; Masande Yalo; Jennifer Nambooze; Carolina H. Pohl; Gabré Kemp; Lekgoana K. Setsiba; Motlalepula G. Matsabisa (Drug Target Insights)
Introduction: Candida albicans biofilm formation contributes significantly to antifungal resistance, necessitating new treatment strategies. Annona muricata Lin., a traditional herbal remedy, has shown promise in combating microbial infections. This study evaluated the antibiofilm activity of the methanol extract of A. muricata leaves, alone or combined with fluconazole, against C. albicans.